An upper limit for the τ-neutrino mass from τ → 5π±vτ decays - Ackerstaff,K; Alexander,G; Allison,J; Altekamp,N; Anderson,KJ; Anderson,S; Arcelli,S; Asai,S; Ashby,SF; Axen,D; Azuelos,G; Ball,AH; et al. (European Physical Journal C, 1998)
An upper limit for the τ-neutrino mass has been determined from the decay τ → 5π±vτ using data collected with the OPAL detector from 1991 to 1995 in e+e- collisions at √s ≈ Mz. A limit of 43.2 MeV at 95% CL is obtained using a two-dimensional method in the 5π invariant mass and energy distribution from 22 selected events. Combining this result with OPAL's previously published measurement using τ+ τ- → 3h±vτ + 3hvτ decays, a new combined limit of mvτ < 27.6 MeV (95% CL) is obtained.